Transcriptome analysis reveals that auxin promotes strigolactone-induced adventitious root growth in the hypocotyl of melon seedlings - Li, Jingrui; Fan, Mi; Zhang, Qinqin; Lü, Guiyun; Wu, Xiaolei; Gong, Binbin; Wang, Yubo; Zhang, Ying; Gao, Hongbo (Frontiers in Plant Science, 2023)
Strigolactone (SL) and auxin are two important phytohormones involved in plant root development, but whether they show synergistic or mutual promotion effects during adventitious root (AR) formation has not been adequately explored. In this study, we investigated the mechanisms of GR24 (synthetic SL) and IAA (indole-3-acetic acid, a type of auxin) in the formation of ARs were investigated using melon as the study material. Morphological measurements showed that the AR number, length, superficial area and volume under GR24 treatment were 1.60-3.27, 1.58-3.99, 2.06-3.42 and 3.00-6.11 times greater than those of the control group, respectively, at 6-10 d; GR24 + IAA treatment further promoted AR formation in melon seedlings, and the AR number, length, superficial area and volume under GR24 + IAA treatment were 1.44-1.51, 1.28-1.73, 1.19-1.83, and 1.31-1.87 times greater than those obtained with GR24 treatment, respectively. Transcriptome analysis revealed 2742, 3352, and 2321 differentially expressed genes (DEGs) identified from the GR24 vs. control, GR24 + IAA vs. control, and GR24 + IAA vs. GR24 comparisons, respectively. GR24 treatment and GR24+IAA treatment affected auxin and SL synthesis as well as components of the phytohormone signal transduction pathway, such as auxin, brassinosteroid (BR), ethylene (ETH), cytokinin (CK), gibberellin (GA), and abscisic acid (ABA). The concentrations of auxin, GA, zeatin (ZT), and ABA were evaluated using high-performance liquid chromatography (HPLC). From 6 to 10 d, the auxin, GA, and ZT contents in the GR24 treatment group were increased by 11.48%-15.34%, 11.83%-19.50%, and 22.52%-66.17%, respectively, compared to the control group, and these features were increased by 22.00-31.20%, 21.29%-25.46%, 51.76%-98.96%, respectively, in the GR24+IAA treatment group compared with the control group. Compared to the control, the ABA content was decreased by 10.30%-11.83% in the GR24 treatment group and decreased by 23.12%-31.58% in the GR24 + IAA treatment at 6-10 d. Our study revealed an interaction between strigolactone and auxin in the induction of AR formation in melon seedlings by affecting the expression of genes related to plant hormone pathways and contents.